y=2(x-9)+3

Simple and best practice solution for y=2(x-9)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=2(x-9)+3 equation:


Simplifying
y = 2(x + -9) + 3

Reorder the terms:
y = 2(-9 + x) + 3
y = (-9 * 2 + x * 2) + 3
y = (-18 + 2x) + 3

Reorder the terms:
y = -18 + 3 + 2x

Combine like terms: -18 + 3 = -15
y = -15 + 2x

Solving
y = -15 + 2x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -15 + 2x

See similar equations:

| 5x-20+x*-3=50 | | 2x+18=-16 | | 1=sin(2piT) | | 294-x=216 | | 10x-x^2=y | | 6x+60=50 | | 200=80-v | | -5=1-5n-n | | -7(-x+4)+10(-x)+3(-4x-2)+34= | | -4(2+1)=-5-2(3) | | 3(4c-1)-3=7c+9 | | Y=-7.5x+11 | | 36m+107-3m=36 | | (x-4)+(2x-7)=0 | | 8m=-3m+1 | | V-2x+3y-z=8 | | 0=-15-3y-4x | | 5p-9=2p+21 | | (X+8)=(4X-28) | | 2.5(2+z)=5(z+2.5) | | y=1.5-1 | | A=6F+4g | | 5x-2(7x-1)=14x | | 4Y^2+x^2=4 | | 3a-2=5 | | 4Y^2+x^2= | | 7(X-5)=71 | | 35x+7=11x+4 | | 4z=6z+2 | | Logx=2.4 | | 2x-4y+z=0 | | 8(2z-5)=4n+8 |

Equations solver categories